Pengaruh Firm Size, Debt To Equity Ratio Dan Return On Equity Terhadap Pajak Penghasilan Badan Terutang Sub Sektor Perkebunan Yang Terdaftar Di BEI 2017 - 2021 - Simangunsong, Melati Marguna; Masyitah, Emi (Program Studi Akuntansi, 2023)
The analysis of the variables influencing the amount of corporate income tax due is the goal of this study. Firm Size, Debt to Equity Ratio, and Return on Equity Ratio are the independent variables examined in this study. The corporate income tax that must be paid is the dependent variable. The 24 plantation enterprises listed on the BEI for the years 2017–2021 served as the research population. Seven businesses were chosen as the research samples using the purposive sampling technique. Multiple linear regression analysis was used as the data analysis method in this study, with the SPSS version 26 program. The study's findings indicate that while return on equity ratio and debt to equity ratio have no discernible effects on corporate income tax payable, firm size has a considerable impact on payable corporate income. According to simultaneous test results, the amount of corporate income tax due is influenced by firm size, return on equity, and debt to equity ratio. The study's conclusion is that the corporate income tax payable is significantly impacted by the firm size, debt to equity ratio, return on equity ratio, and both partially and